Grenz ray therapy in disseminated superficial actinic porokeratosis: A case series of 17 patients. (14th December 2021) - Ting, Sarajane; Webster, Michael
Abstract: The treatments available for disseminated superficial actinic porokeratosis (DSAP) have been limited and have variable efficacy. We report the largest case series to date of the use of Grenz ray therapy in 17 patients with DSAP. There was at least 50% improvement in DSAP lesions in all cases. Erythema, itching and burning were common side effects of Grenz ray therapy. We believe that Grenz ray therapy may be an effective treatment option for patients with DSAP.